Pengaruh Pembelajaran Pair Checks Terhadap Kemampuan Berpikir Kritis Siswa - Hanifatul Awwalina; Risdiana Chandra Dhewy; Eka Nurmala Sari Agustina (Program Studi Pendidikan Matematika STKIP PGRI Sidoarjo, 2020)
Pair Checks learning is group learning that can guide partners to think critivally. This research’s purpose is to knowing the effect of Pair Checks Learning to the critical thinking skills of students in solving the story task. This type of this research is the experiment using a quantitative approach. This research was conducted in the academic year 2019/2020 in SMK Informatika Sumber Ilmu Tulangan. The sample of this research were 26 students using purposive sampling technique. The result showed that there was an influence of the pair checks learning on the critical thinking ability of the student because tcount = 3,431 > ttable = 2.064 and supported by significant probability conditions of (0.002) < α (0.05). And because of the line of the regression equation Y = -15,479 + 1.743X which shows that if the learning of Pair checks is implemented better than the critical thinking skills of student will also be better. Pair Checks Learning has a contribution by 32.9% to the critical thinking ability of students. Applying pair check learning make students can argue or be more active in class and improve critical thinking skills that are good for solving mathematical story problems.